Multicenter study on the effect of early screening skills training for autism spectrum disorders in primary care hospitals in Chengdu - Yang Wenxu; Le Jiao; Zhang Lan; Zhang Ying; Yang Ping; Zhao Chunxia; Du Chunhua; He Junni; Cao Yanmei; Shang Jia; Li Li; Liu Yan; et al. (Sichuan jingshen weisheng, 2022)
ObjectiveTo investigate effect of conducting training of autism spectrum disorder （ASD） early screening skill on improving the ability to early identify ASD of medical staffs in primary care hospitals.MethodsIn September 2021， the training of ASD early screening skills was carried out for medical staffs from 20 primary care hospitals in Chengdu. After training， the training effect was evaluated. The numbers of referrals from primary care hospitals to superior hospitals， confirmed ASD as well as their average diagnostic age of children with ASD before and after training were used as evaluation indicators.ResultsAfter training， the number of children with suspected ASD referred by primary care hospitals was more than that before training ［（16.65±11.60） vs. （3.40±2.23）， t=5.431， P<0.01］， the number of children diagnosed with ASD was more than that before training［（6.85±4.93） vs. （2.45±1.67）， t=4.171， P<0.01］， and the differences were statistically significant. As for the diagnosed age of ASD children， after training， the average age was lower than that before training ［（34.95±11.67） vs. （42.2±14.64）， t=-2.553， P=0.019］.ConclusionTraining of ASD early screening skills for medical staffs in primary care hospitals may help to improve their ability to early screening ASD children.